Highlighting fibroblast plasticity in lung fibrosis: the WI-38 cell line as a model for investigating the myofibroblast and lipofibroblast switch - Vásquez-Pacheco, Esmeralda; Marega, Manuela; Lingampally, Arun; Fassy, Julien; Truchi, Marin; Goth, Kerstin; Trygub, Lisa; Taghizadeh, Sara; Bartkuhn, Marek; Alexopoulos, Ioannis; Dong, Ying; Lebrigand, Kevin; et al. (My University, 2024)
Background: Myofibroblasts (MYFs) are generally considered the principal culprits in excessive extracellular matrix deposition and scar formation in the pathogenesis of lung fibrosis. Lipofibroblasts (LIFs), on the other hand, are defined by their lipid-storing capacity and are predominantly found in the alveolar regions of the lung. They have been proposed to play a protective role in lung fibrosis. We previously reported that a LIF to MYF reversible differentiation switch occurred during fibrosis formation and resolution. In this study, we tested whether WI-38 cells, a human embryonic lung fibroblast cell line, could be used to study fibroblast differentiation towards the LIF or MYF phenotype and whether this could be relevant for idiopathic pulmonary fibrosis (IPF). Methods: Using WI-38 cells, Fibroblast (FIB) to MYF differentiation was triggered using TGF-β1 treatment and FIB to LIF differentiation using Metformin treatment. We also analyzed the MYF to LIF and LIF to MYF differentiation by pre-treating the WI-38 cells with TGF-β1 or Metformin respectively. We used IF, qPCR and bulk RNA-Seq to analyze the phenotypic and transcriptomic changes in the cells. We correlated our in vitro transcriptome data from WI-38 cells (obtained via bulk RNA sequencing) with the transcriptomic signature of LIFs and MYFs derived from the IPF cell atlas as well as with our own single-cell transcriptomic data from IPF patients-derived lung fibroblasts (LF-IPF) cultured in vitro. We also carried out alveolosphere assays to evaluate the ability of the proposed LIF and MYF cells to support the growth of alveolar epithelial type 2 cells. Results: WI-38 cells and LF-IPF display similar phenotypical and gene expression responses to TGF-β1 and Metformin treatment. Bulk RNA-Seq analysis of WI-38 cells and LF-IPF treated with TGF-β1, or Metformin indicate similar transcriptomic changes. We also show the partial conservation of the LIF and MYF signature extracted from the Habermann et al. scRNA-seq dataset in WI-38 cells treated with Metformin or TGF-β1, respectively. Alveolosphere assays indicate that LIFs enhance organoid growth, while MYFs inhibit organoid growth. Finally, we provide evidence supporting the MYF to LIF and LIF to MYF reversible switch using WI-38 cells. Conclusions: WI-38 cells represent a versatile and reliable model to study the intricate dynamics of fibroblast differentiation towards the MYF or LIF phenotype associated with lung fibrosis formation and resolution, providing valuable insights to drive future research.
Keywords: ddc:610